Improvement of Environmental, Occupational Health and Safety Performance: A Case Study of a Peruvian Agrochemical Company - Gutiérrez Falcón, Pablo César (2023)
This paper describes the design and implementation of a management system in a Peruvian agrochemical company that resulted in improved environmental, occupational health and safety (EHS) performance. ISO 14001 and ISO 45001 standards, together with relevant national and international standards, were incorporated into the design of the management system, and a module-based implementation scheme supported by staff training was applied. Information on solid waste and electrical energy management, occupational accidents and medical fitness was collected and analyzed using the Shapiro-Wilk and Wilcoxon tests, yielding statistical evidence of improved performance.